The Binding of Alpinia galanga Oil and Its Nanoemulsion to Mammal GABAA Receptors Using Rat Cortical Membranes and an In Silico Modeling Platform - Nattakanwadee Khumpirapang; Krit Suknuntha; Pathomwat Wongrattanakamon; Supat Jiranusornkul; Songyot Anuchapreeda; Petrine Wellendorph; Anette Müllertz; Thomas Rades; Siriporn Okonogi (MDPI AG, 2022)
The anesthetic effect of Alpinia galanga oil (AGO) has been reported. However, knowledge of its pathway in mammals is limited. In the present study, the binding of AGO and its key compounds, methyl eugenol, 1,8-cineole, and 4-allylphenyl acetate, to gamma-aminobutyric acid type A (GABAA) receptors in rat cortical membranes, was investigated using a [3H]muscimol binding assay and an in silico modeling platform. The results showed that only AGO and methyl eugenol displayed a positive modulation at the highest concentrations, whereas 1,8-cineole and 4-allylphenyl acetate were inactive. The result of AGO correlated well to the amount of methyl eugenol in AGO. Computational docking and dynamics simulations into the GABAA receptor complex model (PDB: 6X3T) showed the stable structure of the GABAA receptor-methyl eugenol complex with the lowest binding energy of −22.16 kcal/mol. This result shows that the anesthetic activity of AGO and methyl eugenol in mammals is associated with GABAA receptor modulation. An oil-in-water nanoemulsion containing 20% w/w AGO (NE-AGO) was formulated. NE-AGO showed a significant increase in specific [3H]muscimol binding, to 179% of the control, with an EC50 of 391 µg/mL. Intracellular studies show that normal human cells are highly tolerant to AGO and the nanoemulsion, indicating that NE-AGO may be useful for human anesthesia.